SPECIALIZATION OF ENTERPRISES IN AGRICULTURE AND FORMATION OF OPTIMAL COMPOSITION OF INDUSTRIES - Tolanov Dilyorbek Ulugbek, (International Journal of Innovations in Engineering Research and Technology, 2022)
Specialization is the gathering of labor and material resources for the production of goods of the most economic importance for the market and the provision of services, the wide and effective use of new equipment: the organization of new, advanced technology and labor It creates favorable conditions for the introduction of rental relations and family contract methods, allows to significantly increase the amount of produced products and the type of service, increases labor productivity, raises the production efficiency of farms. full implementation of tasks, i.e. production of advanced, ecologically clean agrotechnics, zoo-veterinary, technical service, organic and mineral fertilizers and plant and livestock protection products, scientific achievements, advanced work experience by introducing and using them effectively.